2018
DOI: 10.1136/bmjopen-2017-020293
|View full text |Cite
|
Sign up to set email alerts
|

Risk of metabolic disorders in childless men: a population-based cohort study

Abstract: ObjectiveTo study whether male childlessness is associated with an increased risk of metabolic disorders such as metabolic syndrome (MetS) and diabetes.DesignA population-based cohort study.SettingNot applicable.Participants2572 men from the population-based Malmö Diet and Cancer Cardiovascular Cohort.InterventionsNone.Main outcome measuresFrom cross-sectional analyses, main outcome measures were ORs and 95% CIs for MetS and diabetes among childless men. In prospective analyses, HRs and 95% CI for diabetes amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 41 publications
1
28
2
Order By: Relevance
“…Research has consistently found that parenthood predicts lower morbidity and mortality among men (Bungum et al 2018;Modig et al 2017). These findings suggests that paternity might be protective for men's health, and opens questions about whether this association is driven by a causal effect of fatherhood and about its potential mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…Research has consistently found that parenthood predicts lower morbidity and mortality among men (Bungum et al 2018;Modig et al 2017). These findings suggests that paternity might be protective for men's health, and opens questions about whether this association is driven by a causal effect of fatherhood and about its potential mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…In a recent study of 2572 Swedish men, an elevated risk of MetS and type 2 diabetes was found in childless men as compared to those men who have fathered one or more children [7]. Having access to a larger cohort of men from background population and a longer follow-up, we wanted to evaluate the metabolic profile of childless men and estimate the risks of major adverse cardiovascular events (MACE) and cardiovascular and all-cause mortality accounting for well known risk factors of cardiovascular disease (CVD) including smoking, alcohol consumption, high body mass index (BMI), dyslipidemia, hypertension, family history of CVD high fasting glucose, and socioeconomic factors.…”
Section: Introductionmentioning
confidence: 97%
“…It has also been shown that men who fathered children following intracytoplasmic sperm injection (ICSI)-which is the preferred method when semen quality is poor-more often is prescribed drug treatment for hypertension, dyslipidemia, and MetS [5]. Married men who have not fathered children, which might reflect impaired fertility, have presented with higher risk of diabetes and cardiovascular disease [6,7]. Therefore, a man's reproductive performance was suggested to be a general health marker [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown an association between male childlessness or infertility and risk of CVD, hypertension, and metabolic syndrome [47,48]. The prevalence of hypogonadism is significantly increased among men with reduced fertility [49].…”
Section: Male Hypogonadism and Cardiovascular Riskmentioning
confidence: 97%